A study on structural and gas adsorptive characteristics of metal oxide modified zeolite adsorbents - 207237 Chieng, Yu Yuan (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2006